FRI0317 Humoral and cellular immunity to varicella-zoster virus in giant cell arteritis patients: no evidence of viral reactivation at onset of disease. (15th June 2017) - Rondaan, C; Geest, K van der; Eelsing, E; Bos, N; Westra, J; Brouwer, E
Abstract : Background: Giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) are strongly overlapping diseases that are thought to have a shared etiology [1]. The observation of varicella-zoster virus (VZV) antigen in temporal artery biopsies of GCA patients led to the hypothesis that VZV might be a trigger for the onset of the disease [2]. Herpes zoster occurs when the latently present VZV reactivates. It has been reported that patients with GCA do not appear to be at increased risk of herpes zoster compared with age and sex matched controls, even during treatment with high dose glucocorticoids [3]. Levels of VZV specific immunoglobulin G (VZV-IgG) are known to only slowly decline again after a reactivation [4]. We therefore hypothesized, in line with the proposed etiologic role, to find higher VZV-IgG levels in GCA and PMR patients at disease onset, compared to healthy controls. Furthermore, we expected to find no differences in cell-mediated immunity to the virus between patients and controls assuming that the incidence of herpes zoster is not increased in GCA. Objectives: To investigate humoral and cellular immunity to VZV in GCA and PMR patients and compare these to results in age-and sex matched healthy controls. Methods: Antibody responses to VZV glycoprotein were measured in serum samples of 35 GCA patients and 26 PMR patients at baseline (before glucocorticoid treatment) and during follow up, and in 58 healthy controls by an enzyme-linked immunosorbent assay (ELISA). Cell-mediated immunity to VZV was determined by performing interferon-γ (IFNγ) enzyme-linked immunosorbent spot (ELISpot) and intracellular cytokine flow cytometry measurements in 11 GCA patients and 15 PMR patients, and in 26 age and sex matched healthy controls. Results: Similar levels of VZV-IgG were found in GCA and PMR patients at baseline, and healthy controls. The number of VZV specific IFNγ spot-forming cells was significantly lower in GCA patients than in healthy controls (p=0.029), but not different in PMR patients compared to healthy controls. Conclusions: Since antibody levels at baseline were not different in GCA and PMR patients compared to healthy controls it seems unlikely that VZV has an important role in the aetiology of GCA or PMR. The finding of a decreased cell-mediated immunity in GCA patients, especially after treatment with high dose corticosteroids may indicate an increased risk of developing herpes zoster. References: Buttgereit F, Dejaco C, Matteson EL, Dasgupta B. Polymyalgia Rheumatica and Giant Cell Arteritis: A Systematic Review. Jama 2016 Jun 14;315(22):2442–2458. Gilden D, Nagel MA. Varicella zoster virus and giant cell arteritis. Current opinion in infectious diseases 2016 Jun;29(3):275–279. Schafer VS, Kermani TA, Crowson CS, Hunder GG, Gabriel SE, Ytterberg SR, et al. Incidence of herpes zoster in patients with giant cell arteritis: a population-based cohort study. Rheumatology (Oxford, England) 2010 Nov;49(11):2104–2108. Cradock-Watson JE, Ridehalgh MK, Bourne MS. Specific immunoglobulin responses after varicella and herpes zoster. The Journal of hygiene 1979 Apr;82(2):319–336. Disclosure of Interest: None declared